What Would It Take to Change an Inference? Using Rubin's Causal Model to Interpret the Robustness of Causal Inferences - Frank, Kenneth A.; Maroulis, Spiro J.; Duong, Minh Q.; Kelcey, Benjamin M. (Educational evaluation and policy analysis, 2013)
We contribute to debate about causal inferences in educational research in two ways. First, we quantify how much bias there must be in an estimate to invalidate an inference. Second, we utilize Rubins causal model to interpret the bias necessary to invalidate an inference in terms of sample replacement. We apply our analysis to an inference of a positive effect of Open Court Curriculum on reading achievement from a randomized experiment, and an inference of a negative effect of kindergarten retention on reading achievement from an observational study. We consider details of our framework, and then discuss how our approach informs judgment of inference relative to study design. We conclude with implications for scientific discourse.